Cervicovaginal Fluid Acetate: A Metabolite Marker of Preterm Birth in Symptomatic Pregnant Women - Amabebe, Emmanuel; Reynolds, Steven; Stern, Victoria; Stafford, Graham; Paley, Martyn; Anumba, Dilly O. C. (Frontiers in Medicine, 2016)
Changes in vaginal microbiota that are associated with preterm birth (PTB) leave specific metabolite fingerprints that can be detected in the cervicovaginal fluid (CVF) using metabolomics techniques. In this study we characterize and validate the CVF metabolite profile of pregnant women presenting with symptoms of threatened preterm labor (PTL) by both 1H-Nuclear Magnetic Resonance spectroscopy (NMR) and enzyme-based spectrophotometry. We also determine their predictive capacity for PTB, singly and in combination with current clinical screening tools – cervicovaginal fetal fibronectin (FFN) and ultrasound cervical length (CL). CVF was obtained by high-vaginal swabs from 82 pregnant women with intact fetal membranes presenting between 24 and 36 weeks (wks) gestation with symptoms of threatened, but not established, PTL. Dissolved CVF samples were scanned with a 400 MHz NMR spectrometer. Acetate and other metabolites were identified in the NMR spectrum, integrated for peak area, and normalized to the total spectrum integral. To confirm and validate our observations, acetate concentrations (AceConc) were also determined from a randomly selected subset of the same samples (n=57), by spectrophotometric absorption of NADH using an acetic acid assay kit. CVF FFN level, transvaginal ultrasound CL, and vaginal pH were also ascertained. Acetate normalized integral and AceConc were significantly higher in the women who delivered preterm compared to their term counterparts (P=0.002 and P=0.006 respectively). The 1H-NMR-derived acetate integrals were strongly correlated with the AceConc estimated by spectrophotometry (r=0.69; P<0.0001). Both methods were equally predictive of PTB <37 wks (acetate integral: AUC=0.75, 95% CI=0.60-0.91; AceConc: AUC=0.74, 95% CI=0.57-0.90, optimal predictive cut-off of >0.53 g/l), and of delivery within 2 weeks of the index assessment (acetate integral: AUC=0.77, 95% CI=0.58-0.96; AceConc: AUC=0.68, 95% CI=0.5-0.9). The combination of CVF acetate, FFN and ultrasound CL in a binary logistic regression model improved the prediction of PTB compared to the 3 markers individually. Elevated CVF acetate in women with symptoms of PTL appears predictive of preterm delivery, as well as delivery within 2 weeks of presentation. An assay of acetate in CVF may prove of clinical utility for predicting PTB.